Thermodynamic, Economic and Emissions Analysis of a Micro Gas Turbine Cogeneration System operating on Biofuels - Kunte, Benjamin [UNESP] (2015)
The most promising methods to reduce greenhouse gases as well as counteract against the imminent depletion of fossil fuels are: a) the use of alternative fuels obtained from biomass, such as biogas or bio-syngas; b) enhancing the power plant efficiency by decreasing the percentage of useful energy lost to the environment. Whereas efficiency optimisation of a particular machine in a power plant, e.g. gas turbine or compressor, is a very longsome development, cogeneration can quickly and significantly increase the overall efficiency of a power plant. In this work, energetic, exergetic, emissions and economic analyses of a cogeneration system consisting of a 200 kW micro gas turbine combined with a heat recovery steam generator are introduced and conducted. Furthermore, biogas and syngas operation are compared to natural gas operation, to investigate the adequacy of these two alternative fuels for use in micro gas turbines. The proposed cogeneration plant proved to be technically feasible for all fuels, because the selected micro gas turbine Capstone C200 is available in various, fuel-specific versions with optimised fuel injection systems. The plant presented overall energetic efficiencies of 50.9%, 48.6% and 47.9% for natural gas, biogas and syngas operation, respectively. Due to very high natural gas and syngas prices, the cogeneration plant presented economic feasibility only in case of biogas operation, with short payback periods of approximately 2.8 years and high expected annual saving. Moreover, biogas has the highest ecologic efficiency and was therefore found to be the best alternative to fossil fuels.